Nine Channels Temperature Data Logger Design for Dry Sterilizer Calibration - Syaifudin Syaifudin; Dyah Titisari; Tanuj Kumar (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
In the process of sterilizing medical devices, a sterilizer that is able to produce an accurate and even temperature is needed. If the resulting temperature is not in accordance with the regulated temperature and is not evenly distributed, it will be fatal/damage to the material sterilized. Periodic calibration should be applied to the sterilizer to monitor its function. Based on the research that has been done, no one has done research on making a temperature data logger with 9 channels to calibrate the sterilizer. This study aims to design a temperature measuring device with 9 sensors that can measure simultaneously, so that the accuracy and the distribution of the temperature of a sterlisator can be obtained. This tool used a K thermocouple-type temperature sensor which will detect the temperature and further enters the analog signal conditioning circuit. This then enters the ATMegga 2560 which has been programmed and processed in such a way, leading to the display of the temperature on the 4x20 character LCD. Temperature measurement data will be further stored to SD Card every 10 seconds in the form of a txt file. Tests were carried out on sterilizers, continued by comparison with the Madgetech OctTemp2000 data logger. Based on the measurement and comparison data, the average error was obtained at a temperature of 50ºC with the smallest error value of 0.7% and the largest error value of 3.9%. At a temperature of 100ºC, the smallest error value is 1.6% and the largest error value is 10.5%. Furthermore, at a temperature of 120ºC, the smallest error value is 0.0% and the largest error value is 8.5%. The module resulting from this research is stable in response to temperature by looking at the very small uncertainty value. This research can be further used to help analyze the temperature distribution in a sterilizer. With these measurement results, this study is considered having a fairly high error value at several measurement points.